Hubungan antara tabiat belajar dengan pencapaian akademik di kalangan pelajar : satu kajian kes di fakulti kejuruteraan Universiti Malaysia Sarawak (UNIMAS) - Chew, Wei Lian. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This research is conducted to investigate the influece of study habits to students' academic achievement in Faculty of Engineering Universiti Malaysia Sarawak. The main aim of this research was to identify how strong the correlation between the four categories of the study habits toward students' academic achievement. Four categories of the study habits that have been used as the independent factors are Time Management, Note Taking, Assignment Preparation and Examination Preparation. A set of questionnaires has been used for the purpose of collecting data. The questions used in this questionnaire were adopted from the previous researches that have been conducted by the past researchers. These questions divided into five parts. The questions in part A were about demographic factors of respondents, part B, C, D and E were about the four categories of study habits that been studied. There were 50 respondents from engineering students involved in this study. The data collected was analyzed by using computer software, Statistical Package for Social Science (SPSS) Window Release Version 11.5. Result from Pearson Correlation analysis found that three out of four categories study habits have sighnificant relationship to the students' academic achievement. However the relationship appeared strongly moderate towards students' academic achievement